2015
DOI: 10.5772/60500
|View full text |Cite
|
Sign up to set email alerts
|

Facile Nanostructured Substrate Preparation Using Gold Nanocuboids for SERS

Abstract: In the present work, we report a practical fabrication method of gold-aluminium substrates for surface enhanced Raman spectroscopy. A commercial aluminium-foil was used to fabricate SERS substrates by depositing gold nanocuboids and faceted particles onto their surfaces using the drop-drying method. The gold nanoparticles were characterized by ultraviolet-visible spectroscopy, while the size and morphology were determined by field emission scanning electron microscopy. The performance of the substrates was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…37 The results show that the AuNPs prepared using the automated loop flow-reactor technology as SERS substrates have comparable EFs and detection limits for the RG6 detection compared to laboratory methods. 38 The actual minimum concentration of the AuNPs prepared by the ring-flow analysis method for the RG6 solution was 1 × 10 −9 M, which is similar to that of the AuNPs of similar shape and size mentioned in the literature. 39…”
Section: Resultssupporting
confidence: 77%
“…37 The results show that the AuNPs prepared using the automated loop flow-reactor technology as SERS substrates have comparable EFs and detection limits for the RG6 detection compared to laboratory methods. 38 The actual minimum concentration of the AuNPs prepared by the ring-flow analysis method for the RG6 solution was 1 × 10 −9 M, which is similar to that of the AuNPs of similar shape and size mentioned in the literature. 39…”
Section: Resultssupporting
confidence: 77%
“…The estimated average sizes were (a) 36 ± 5 nm (90 μL), (b) 42 ± 5 nm (60 μL), (c) 46 ± 7 nm (40 μL), (d) 55 ± 9 nm (20 μL), (e) 63 ± 5 nm (10 μL), and (f) 85 ± 8 nm (5 μL) , respectively. 2022 When a small volume of seeds is added to the growth solution, large-sized CGNCs grow, and conversely, smaller sized CGNCs were obtained using a large volume of seeds. The size of CGNCs as a function of seeds shows an exponential behavior (see Supplementary Figure S1 in the supplementary material).
Figure 1.Micrographs and sizes histograms of the concave gold nanocubes: (a) 36 ± 5 nm, (b) 42 ± 5 nm, (c) 46 ± 7 nm, (d) 55 ± 9 nm, (e) 63 ± 5 nm, and (f) 85 ± 8 nm.
…”
Section: Resultsmentioning
confidence: 99%
“…To prepare the SERS substrate, a thin film of AgNPs/AuNPs was deposited onto the polished surface of a square-sized Al plate by drop-casting (Martínez-Torres et al, 2015) of the aqueous solution of NPs followed by spontaneous evaporation of the solvent (Fig. 1).…”
Section: Preparation Of Samples For Sers Measurementsmentioning
confidence: 99%
“…Therefore, the thin film of AgNPs seems to be more efficient in producing the Raman enhancement of R6G in agreement with the hypothesis of superactive hotspots formation (Kleinman et al, 2013). Martínez-Torres et al (Martínez-Torres et al, 2015) reported enhancement factor as ~ 10 6 using a solution of R6G on Al-foil where Au nanocuboids have been drop cast and allowed to dry spontaneously. Martinez-Garcia et al (2016) measured EF in the order of ~ 10 7 using the drop-dry method to obtain dried concave gold nanocubes solution on Al-6063 slides on which the drop of the sample (R6G) had subsequently dried.…”
Section: Fig 3 Uv-vis Absorption Spectrum Of Chemically Synthesized Agnps (Red Line) Commercially Available Agnps (Black Line) and Aunps mentioning
confidence: 99%